Effect of Sodium chloride concentrations on the Growth and Some Organic Chemical Compounds of Barley Hordeum vulgaris L. - Muhsin Athbi, Ahmed (University of Thi-Qar Journal of Science, 2010)
An experiment in plastic pots was conducted to know the effect of different salt concentration levels ( 3 , 6 , 9 and 12 ) ds/m of sodium chloride in addition to distill water as a control treatment on the growth and some organic chemical compounds of barley plant ( local variety ) cultivated in Iraq . The results of the study shows an increase on the salt concentration levels causing a gradual decrease on the growth of plant in terms of stems heights (11.5-4.3 cm), water content percentages (87.6-85.0 %) and dry matter weights at the all salinity treatments as compared with distilled water at a control treatment , and increasing in the carbohydrates (1.5- 2.5 µg/gm), proteins (12.3-15 µg/gm) and proline (7.8-12.4 µg/gm) concentrations whereas the different patterns of a significant differences were observed between the all salinity treatments .